Non-invasive Respiratory Support of the Premature Neonate: From Physics to Bench to Practice - Sammour, Ibrahim; Karnati, Sreenivas (Frontiers in Pediatrics, 2020)
Premature births continue to rise globally with a corresponding increase in various morbidities among this population. Rates of respiratory distress syndrome and the consequent development of Bronchopulmonary Dysplasia (BPD) are highest among the extremely preterm infants. The majority of extremely low birth weight premature neonates need some form of respiratory support during their early days of life. Invasive modes of respiratory assistance have been popular amongst care providers for many years. However, the practice of prolonged invasive mechanical ventilation is associated with an increased likelihood of developing BPD along with other comorbidities. Due to the improved understanding of the pathophysiology of BPD, and technological advances, non-invasive respiratory support is gaining popularity; whether as an initial mode of support, or for post-extubation of extremely preterm infants with respiratory insufficiency. Due to availability of a wide range of modalities, wide variations in practice exist among care providers. This review article aims to address the physical and biological basis for providing such support, along with current clinical evidence.